The RATIONALITY OF USE ACYCLOVIR IN PERMATA PERMATA CLINIC, TANGERANG SELATAN CITY, JUNE-DECEMBER 2020 PERIOD: RASIONALITAS PENGGUNAAN OBAT ACYCLOVIR DI KLINIK INSAN PERMATA KOTA TANGERANG SELATAN PERIODE JUNI-DESEMBER 2020 - Sayyidah, Sayyidah; Aulia , Gina; Kristiyowati , Anis Dwi (Jurnal Kesehatan Masa Depan, 2022)
Abstract Rationality of Drug Use is the administration of drugs that refers to the right diagnosis, the right indication, the right drug, the right dose, the right manner of giving and the right old proper gifts. Acyclovir is a synthetic purine nucleoside analogue drug. The antiviral properties of acyclovir are limited to the herpes virus group as well as mechanism of action is selectively. The purpose of this study was to determine know patient age, gender doctor diagnosis, the type of availability of prescription drugs acyclovir, the rationality based on the accuracy of the diagnosis, the accuracy indication, the accuracy of the drug, the accuracy of the dose, the accuracy manner of giving and the accuracy old proper gift. The design of this research is descriptive, namely research by observing the data that is already available with a descriptive method design. The data was obtained from tracing medical record data using a retrospective and total samplingThe sample of this study was 80 taken from Medical Records in June-December 2020 to be analyzed descriptively to explain the rationality of use acyclovir drug. Based on the results of research from the Insan Permata Clinic, it was found who used acyclovir drug were predominantly male, with 50 patients with a percentage of 62.5% while in women around 30 patients with a percentage of 37.5%. using acyclovir drug experienced by pediatric patients aged 6-17 years with 29 patients for the percentage there were 0.03625%. This is in accordance with the theory that infections often occur more severely in toddlers and children than adults. This is due to the immature immune system at a young age. Keywords: Acyclovir, Antivirus, Rational